SISTEM PENGAMAN PINTU OTOMATIS MENGGUNAKAN RADIO FREQUENCY IDENTIFICATION (RFID) TAG CARD DAN PERSONAL IDENTIFICATION NUMBER (PIN) BERBASIS MIKROKONTROLER AVR ATMEGA 128 - Rurungan, Jeprianto; Nugraha, Deny Wiria; Anshori, Yusuf (-)
Abstract Installation of security devices using sensors detectors continuous to grow. Making security system using Passive Infrared censor as the detector can be the right choice. This study formulates the problem Passive Infrared sensor how to work, and can detect the movement and how to utilize a Passive Infrared censor as a security tool room that triggered the short message service for Mobile, which then activates the lights and alarms. The purpose of this research is to investigate how the sensor Passive Infrared detector as a tool and how to use a Passive Infrared sensor as a security tool room that triggered SMS to Mobile, turn on the lights and alarms. The method used in this study is a qualitative method based on the experimental and the author makes a security system using passive infrared censor and short message service as a security tool room by utilizing the output voltage of 5 volts DC output passive infrared which is then processed by a microcontroller and microcontroller ordered wavecom modem to send short message service after the command is executed then the microcontroller triggers TIP 31 transistor to activate the relay so the lights and the alarm is active. Â  Keywords: Security, censors, Passive Infrared, Short Message Service Detectors, and Mobile